All‐Solid‐State Batteries: New Cost‐Effective Halide Solid Electrolytes for All‐Solid‐State Batteries: Mechanochemically Prepared Fe3+‐Substituted Li2ZrCl6 (Adv. Energy Mater. 12/2021). Issue 12 (25th March 2021) - Kwak, Hiram; Han, Daseul; Lyoo, Jeyne; Park, Juhyoun; Jung, Sung Hoo; Han, Yoonjae; Kwon, Gihan; Kim, Hansu; Hong, Seung‐Tae; Nam, Kyung‐Wan; Jung, Yoon Seok
Abstract : In article number 2003190, Kyung‐Wan Nam, Yoon Seok Jung and co‐workers develop a new halide solid electrolyte, Fe 3+ ‐substituted Li2 ZrCl6, that is mechanically sinterable, (electro)chemical‐oxidation tolerant, and free of rare‐earth metals. The outstanding performance of the all‐solid‐state batteries using LiCoO2 and LiNi0.88 Co0.11 Al0.01 O2 is enabled by the use of the newly developed halide superionic conductors.